Failure analysis of corrugated metal hose under ultimate repeated bending process. (January 2020) - Hao, Zengliang; Luo, Junting; Jin, Yongbo; Wei, Wei; Liu, Lei
Highlights: The ultimate repeated bending deformation causes the hose to crack at the wave trough. Cracks propagate from the inner surface of the wave trough to the outer surface. The intergranular brittle fracture, dimple fracture and quasi-cleavage fracture occurred. Abstract: The soft-connected corrugated metal hose in the oxygen lance of metallurgical converter ruptured prematurely at the waveform trough of the fixed end, and the adjacent waveforms at the fixed end extruded each other. The ultimate repeated bending processes of the corrugated metal hose was simulated on the basis of the MARC finite element software. Stress and strain distributions of the corrugated metal hose during the bending process were obtained. The ultimate repeated bending experiment of the hose under alternating loads was performed. The hardness values on each part of the waveforms at the fixed end were tested, and the micro-morphology of the fracture and adjacent area was analyzed by scanning electron microscopy. The experimental results verify the accuracy of the finite element simulation. The failure point of the corrugated metal hose was located at the wave trough during the ultimate repeated bending process, and the cracks at the trough were distributed along the circumferential direction and propagated from the internal surface of the wave trough to the external surface. The crack propagation and fracture models at the wave trough of the hose were established, and the failure mechanism of the hose under the ultimate repeated bending deformation was characterized.